Research on the safe utilization of agricultural water resources in the Yellow River Basin - Yanbin Li; Xuefang Du; Daoxi Li; Xiuyu Zhang (Water Supply, 2022)
Considering the current problems related to the utilization of agricultural water resources in the Yellow River Basin, we propose the definition of the safe utilization of agricultural water resources based on the summary and analysis of recent studies on water resources security. Through the analysis of water resources development and utilization in the basin over the years, an evaluation index system for agricultural water resources security in the basin was constructed, and a weighted cooperative game method combination was used to evaluate the agricultural water resources security in the basin using the weighted TOPSIS model. The evaluation results show that the utilization of agricultural water resources in the areas under the jurisdiction of Sichuan and Shandong Provinces in the basin was in a secure or a relatively higher state, whereas Ningxia was in a relatively unsecure state, and the remaining provinces were in a basic secure state. Based on the evaluation results, we have provided the corresponding countermeasures for the safe utilization of agricultural water resources in terms of water-saving irrigation technology, water resources monitoring system, and water resources management system to support the effective implementation of efficient water-saving irrigation of agricultural water resources in the Yellow River Basin. HIGHLIGHTS The definition of safe water utilization in agriculture is proposed.; An index system suitable for the safe utilization of agricultural water resources in the Yellow River Basin is constructed.; The corresponding countermeasures for the safe utilization of agricultural water resources are put forward from the aspects of agricultural water use mode and water-saving irrigation technology.;